Osimertinib-induced cutaneous vasculitis: A case report and review of the literature - Hilário Soldin, Inês (2024)
A 77-year-old patient with a history of stage IVa (cT4N3M1a) lung adenocarcinoma, treated with osimertinib 80 mg/day, developed palpable purpura nine days after starting therapy. Skin biopsy revealed leukocytoclastic vasculitis. A complete clinical and lab workup for systemic involvement was unremarkable. The patient suspended osimertinib and started on methylprednisone 1mg/Kg/day. Skin lesions gradually improved. Four weeks apart, the patient resumed osimertinib 40 mg/day along with prednisolone in a slow taping down scheme until 0.5 mg/Kg/day, without vasculitis relapse. After five months of follow-up, there is a good tolerance and a partial response to treatment. This is the first reported case of cutaneous vasculitis induced by osimertinib described in Portugal and the fourth case reported worldwide. Furthermore, this is the first report in which the osimertinib at a dose of 40 mg daily was rechallenged along with corticosteroid therapy.